PHOMOPSIS, SP. COLECIONADO SOBRE PLANTAS CITRICAS EM PIRACIABA E GUARUJÃ - Saccá, Rosário Averna (REVISTA DE AGRICULTURA, 2016)
PHOMOPSIS, SP. COLECIONADO SOBRE PLANTAS CITRICAS EM PIRACIABA E GUARUJÃ